2022
DOI: 10.1097/aln.0000000000004142
|View full text |Cite
|
Sign up to set email alerts
|

General Anesthesia versus Sedation, Both with Hemodynamic Control, during Intraarterial Treatment for Stroke: The GASS Randomized Trial

Abstract: Background It is speculated that the anesthetic strategy during endovascular therapy for stroke may have an impact on the outcome of the patients. The authors hypothesized that conscious sedation is associated with a better functional outcome 3 months after endovascular therapy for the treatment of stroke compared with general anesthesia. Methods In this single-blind, randomized trial, patients received either a standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 23 publications
1
81
1
2
Order By: Relevance
“…Figure 1 shows the various reasons for study exclusion after full-text screening. Finally, six RCTs involving 883 patients undergoing EVT published from 2016 to 2022 were included in this meta-analysis (14)(15)(16)(17)(18)(19). Study characteristics are described in Table 1.…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the various reasons for study exclusion after full-text screening. Finally, six RCTs involving 883 patients undergoing EVT published from 2016 to 2022 were included in this meta-analysis (14)(15)(16)(17)(18)(19). Study characteristics are described in Table 1.…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
“…The median or mean age of the participants ranged from 60 to 73 years with a proportion of male gender being 44-66%. The six studies that provided details regarding the baseline NIHSS score (range: 13-20) all reported no difference between the GA and CS groups (14)(15)(16)(17)(18)(19). The sample size of individual RCT varied between 40 and 345.…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In einer multizentrischen randomisierten Studie untersuchten nun Maurice et al. und das „French Society of Anesthesiologists Research Network“ [ 8 ] die Effekte der Allgemeinanästhesie im Vergleich zur alleinigen Sedierung bei Patientinnen und Patienten, die aufgrund eines Hirninfarktes bei zugrunde liegendem proximalen Gefäßverschluss eine endovaskuläre Therapie erhielten. Die Studie rekrutierte in 4 Zentren in Frankreich und konnte 351 Betroffene einschließen.…”
Section: Endovaskuläre Therapie Des Hirninfarktes: Peri- Und Postproz...unclassified
“…In dieser ersten multizentrischen randomisierten Studie von Maurice et al. [ 8 ] waren die Allgemeinanästhesie und die alleinige Sedierung mit dem gleichen Behandlungsergebnis, bezogen auf den Grad der funktionellen Beeinträchtigung nach 3 Monaten, assoziiert. Die Überlegenheit eines dieser beiden Verfahren lässt sich somit nicht ableiten.…”
Section: Endovaskuläre Therapie Des Hirninfarktes: Peri- Und Postproz...unclassified